Medieval Anti-Semitism, Weimar Social Capital, and the Rise of the Nazi Party: A Reconsideration - Timothy W. Guinnane; Philip Hoffman (Center for Economic Studies and ifo Institute (CESifo), 2022)
The persistence literature in economics and related disciplines connects recent outcomes to events long ago. This influential literature marks a promising development but has drawn criticism. We discuss two prominent examples that ground the rise of the Nazi Party in distant historical roots. Several econometric, analytical, and historical errors undermine the papers' contention that deeply rooted culture and social capital fueled the Nazi rise. The broader lesson is that research of this type works best when it incorporates careful econometrics, serious consideration of underlying mechanisms (including formal theory), and, most important, scrupulous attention to history and to the limitations of historical data.
Keywords: C18; D71; D72; D85; D91; L14; N01; N13; N14; Z10; Z12; 330; historical persistence; medieval pogroms; social capital; culture; networks; Nazism; voting behavior; anti-Semitism; political parties; religion; empirical economics; data based estimates; econometrics